2011
DOI: 10.1007/s12348-010-0003-9
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal artery occlusion in Wegener's granulomatosis: a diagnostic dilemma

Abstract: PurposeTo report a case of central retinal artery occlusion (CRAO) in a patient with biopsy-verified Wegener's granulomatosis (WG) with positive C-ANCA.MethodsA 55-year-old woman presented with a 3-day history of acute painless bilateral loss of vision; she also complained of fever and weight loss. Examination showed a CRAO in the left eye and angiographically documented choroidal ischemia in both eyes.ResultsThe possibility of systemic vasculitis was not kept in mind until further studies were carried out; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“… 11 Tarsal conjunctivitis can be associated with nasolacrimal duct obstruction and subglottic stenosis. 5 , 11 Robinson et al reported conjunctivitis in 16% of Wegener patients. 11 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 11 Tarsal conjunctivitis can be associated with nasolacrimal duct obstruction and subglottic stenosis. 5 , 11 Robinson et al reported conjunctivitis in 16% of Wegener patients. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The most common manifestations are orbital disease (18/140, 15%) followed by scleral (7%), episcleral (3.5%), corneal (8%), and nasolacrimal (7%) abnormalities. 5 , 8 Conjunctivitis in GPA may be ulcerative and necrotic and can cause cicatricial changes in the ocular surface. 9 , 10 Areas of necrosis, active fibrovascular changes, and fibrovascular scars can be seen with tarsal conjunctivitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ophthalmologists may be the first clinicians to encounter GPA patients because ocular manifestations, particularly necrotizing scleritis, may be the first sign of the disease. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%